The lost house - Larsen, Melissa (Minotaur books, 2025)
"In Melissa Larsen's The Lost House comes the mesmerizing story of a young woman with a haunting past who returns to her ancestral home in Iceland to investigate a gruesome murder in her family. Forty years ago, a young woman and her infant daughter were found buried in the cold Icelandic snow, lying together as peacefully as though sleeping. Except the mother's throat had been slashed and the infant drowned. The case was never solved. There were no arrests, no conviction. Just a suspicion turned into a certainty: the husband did it. When he took his son and fled halfway across the world to California, it was proof enough of his guilt. Now, nearly half a century later and a year after his death, his granddaughter, Agnes, is ready to clear her grandfather's name once and for all. Still recovering from his death and a devastating injury, Agnes wants nothing more than an excuse to escape the shambles of her once-stable life-which is why she so readily accepts true crime expert Nora Carver's invitation to be interviewed for her popular podcast. Agnes packs a bag and hops on a last-minute flight to the remote town of Bifröst, Iceland, where Nora is staying, where Agnes's father grew up, and where, supposedly, her grandfather slaughtered his wife and infant daughter. Is it merely coincidence that a local girl goes missing the very same weekend Agnes arrives? Suddenly, Agnes and Nora's investigation is turned upside down, and everyone in the small Icelandic town is once again a suspect. Seeking to unearth old and new truths alike, Agnes finds herself drawn into a web of secrets that threaten the redemption she is hell-bent on delivering, and even her life-discovering how far a person will go to protect their family, their safety, and their secrets. Set against an unforgiving Icelandic winter landscape, The Lost House is a chilling and razor-sharp thriller packed with jaw-dropping twists that will leave you breathless"--